Swimming pedagogy and a curriculum for stroke development (in electromic book format) - Rushall, B. S. (2006)
This book is inspired by the observation that few swimming coaches know much about teaching motor skills, perhaps the single most-important characteristic of an effective swimming coach. It covers two extents of teaching: altering an established movement skill and implementing a total curriculum for developing competitive swimming strokes. Some coaches are so focused on physical conditioning as being the avenue for swimming performance improvements, that the structuring of programs is treated meticulously and according to "exact" formulations, so that it outwardly appears to be a very exact science. However, such an approach is based on several false premises and/or the denial of some important performance principles. This book attempts to focus on the important factors involved in teaching when coaching swimming. It describes swimming pedagogy.